Study regarding the modern management systems, methods and techniques - Bogdan-Alexandru Furduescu (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 6th Edition of the International Symposium, November 2015, Bucharest, 2015)
In this article, I point out that the management systems, methods and techniques are the actual ways used to solve the problems arising from the management functions and which trigger the component activities of the organization functions. The classification of the management systems, methods and techniques includes all the activities by which the structural framework appropriate to the profile and tasks from farms is performed and the activities that ensure the normal work processes. The adoption of modern management systems, methods and techniques, allowing the involvement of execution personnel in managerial act without breaking the authority principles and the innovation promoting, can influence the management style, imparting a democratic character, beneficial to the performance of a farm.
Keywords: 330; systems; methods; techniques; modern management; farm